Stent-Retriever Thrombectomy in STEMI With Large Thrombus Burden - Rafail A. Kotronias, MBChB, MSc; Jason L. Walsh, MBChB; Stefano Andreaggi, MD; Leonardo Portolan, MD; Alessandro Maino, MD; Federico Marin, MD; Jason Chai, MBBCh; Ikboljon Sobirov, MSc; Muhammad Sheikh, MD; Thomas J. Cahill, MBBS, DPhil; Andrew J. Lucking, MBChB, PhD; Max Costello, BSc; et al. (JACC: Advances, 2025)
Background: Percutaneous coronary intervention (PCI) restores epicardial flow in ST-segment elevation myocardial infarction (STEMI), but large thrombus burden (LTB) can impair myocardial perfusion due to embolization. While manual aspiration (MA) devices have limited efficacy in STEMI, the success of stent-retriever thrombectomy (SRT) in stroke suggests it as a promising option for STEMI. Objectives: The RETRIEVE AMI (stent-retriever thrombectomy for thrombus burden reduction in patients with acute myocardial infarction) trial assessed the safety and efficacy of Solitaire X SRT vs Export MA in STEMI patients with LTB. Methods: This single-center study enrolled 81 STEMI patients with LTB (TIMI thrombus grade ≥4) and randomized them to PCI, MA-assisted, or SRT-assisted PCI. The primary endpoint was difference in prestent thrombus volume by optical coherence tomography between SRT and either comparator; coprimary endpoints included device-related target vessel complications and major adverse cardiac and cerebrovascular events through 6 months. Results: SRT was performed in 26 cases (one crossover), and MA in 27. No device-related arterial complications or cerebrovascular events occurred in the SRT arm. Baseline thrombus volume was significantly higher in the SRT group (18.3 mm3) compared to MA (7.7 mm3) and no modification (9.8 mm3; P = 0.04). Prestent thrombus volume was not significantly different between SRT (7.7; IQR: 2.3-18.6) and either MA (4.8; IQR: 1.8-8.4; P = 0.17) or no thrombus modification (9.8; IQR: 4.5-18.1; P = 1.00). Both techniques significantly reduced prestent thrombus burden (SRT: 12.8%; IQR: 4.4%-21.5%; P = 0.016 and MA: 13.0%; IQR: 3.8%-19.4%; P = 0.003) compared to no modification (22.8%; IQR: 10.4%-27.7%). No device-related clinically relevant arterial injury was detected and in-hospital and 6-month major adverse cardiac and cerebrovascular events did not differ between arms. Conclusions: RETRIEVE AMI demonstrates the feasibility of Solitaire X SRT in STEMI with LTB. Prestent thrombus volume was not different between SRT, MA, or no thrombus modification, although SRT extracted larger thrombus volume than MA. Larger multicenter studies using optical coherence tomography-based criteria are needed to minimize variability and enhance comparative assessments.